z = ( sin 2 0 1 5 π + i cos 2 0 1 5 π ) 2 0 1 5 , ( − z ) 2 0 1 5 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
why you common i in first line?
Log in to reply
To obtain a expression of the form cos θ + i sin θ , and then apply DeMoivre's Theorem.
Notice that 1/i = -i
I may be forgetting something, however, shouldn't z be in the form c o s π + i s i n π rather than c o s π − i s i n π ?
Log in to reply
It can also be of the form cos θ − i sin θ , because it comes from cos ( − θ ) + i sin ( − θ ) .
Problem Loading...
Note Loading...
Set Loading...
z = ( i ( cos 2 0 1 5 π − i sin 2 0 1 5 π ) ) 2 0 1 5 z = i 2 0 1 5 ( cos π − i sin π ) z = − i ( − 1 ) z = i − z = − i ( − z ) 2 0 1 5 = ( − i ) 2 0 1 5 ( − z ) 2 0 1 5 = i